A Case of Bullous Skin Disease Presenting with Odynophagia: A Diagnostic Challenge - G. Kravvas; D. Veitch; C. M. Perrett (Case Reports in Dermatological Medicine)
We report a case of Epidermolysis Bullosa Acquisita (EBA) that presented as a diagnostic challenge. A 60-year-old Qatari lady presented with odynophagia, oral ulceration, and weight loss. Multiple physicians investigated her for over 6 months with a multitude of tests and serial gastroscopies, all of which failed to reach a conclusive diagnosis. Only after referral to a dermatologist and full body examination was diagnosis finally achieved. After reviewing the literature, we provide a summary of EBA and highlight the importance of comprehensive clinical reviews in order to avoid unnecessary morbidity.